1995
DOI: 10.1111/j.1432-1033.1995.tb20530.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of Actin Synthesis in Hepatocytes by Transcriptional and Posttranscriptional Mechanisms

Abstract: Treatment of rat hepatocytes with the filamentous-actin-stabilizing toxin phalloidin decreased the amount of globular actin by 77% in the cytosol and by 80% in the nucleus within 12 h. Simultaneously, actin mRNA was specifically increased by 230%. The de-novo synthesis of actin mRNA, as measured by nuclear run-on transcription, was enhanced by 250%. Treatment of cells with actinomycin D blocked the increase of actin mRNA. The apparent half-life of actin mRNA was not significantly altered during treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Autoregulation of actin synthesis by the level of monomeric Gactin or polymeric F-actin has been demonstrated recently in primary cultures of rat hepatocytes [13,14]. To prove whether Gactin is responsible for this regulation, the cellular level of monomeric actin was increased by microinjection into isolated cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Autoregulation of actin synthesis by the level of monomeric Gactin or polymeric F-actin has been demonstrated recently in primary cultures of rat hepatocytes [13,14]. To prove whether Gactin is responsible for this regulation, the cellular level of monomeric actin was increased by microinjection into isolated cells.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently demonstrated that autoregulation of actin synthesis in cultured hepatocytes is due to transcriptional as well as post-transcriptional mechanisms depending on the increase or decrease in the G-actin\F-actin equilibrium effected by C2 toxin and phalloidin [14]. However, it could not be excluded that direct effects of the toxins might influence actin synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hepatocytes (1i10() were used for isolation of nuclei for the nuclear run-on assay. The isolation procedure was performed as described previously [27]. The nuclear run-on reaction was performed with 2i10' nuclei in a vol.…”
Section: Isolation Of Nuclei From Rat Hepatocyte Cultures and Nuclearmentioning
confidence: 99%